(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
The research has to contextualize in the problem generated by the lack of generational replacement and in the search for imaginative alternatives that promote access to new farmers. It focuses on a territory, the Basque Country, and starts from an antecedent, the horticulture park, a model that is showing some deficiencies, mainly caused by the lack of maturity of the new farmer’s project. The search for solutions leads to consider the need to promote the creation of a space where the person who wants to make a living from agriculture can test it. The proposal connects with the agricultural test-space initiative. The results highlight four main commitments: the decision that the Rural Development Associations will manage the test space; the social protection of the tester through a two-year training contract; the tutoring of the tester following patterns similar to those used in the Young Farmers Plan; and the financing of the test space.